Financial fiasco : how America's infatuation with homeownership and easy money created the economic crisis - Norberg, Johan, 1973- (Cato Institute, 2012)
Now newly expanded, with a with a new chapter on the spreading global economic crisis, Financial Fiasco guides readers through a world of irresponsible behavior by consumers, decisionmakers in companies, government agencies, and political institutions.